The crystal structure of [(tetra-μ2-2,6-difluorobenzoato-κ2O:O′)-bis-(2,6-difluorobenzoato-κ2O:O′)-bis-(1,10-phenanthroline-κ2N:N′)]dierbium(III) C66H34N4O12F12Er2 - Yu-Fei, Zhong; Wen-Min, Wang; Xiong-Xin, Peng; Guang-Ming, Bao; Chun-Yan, Hu; Hou-Qun, Yuan (Zeitschrift für Kristallographie. New crystal structures, 2020)
C66H34N4O12F12Er2, triclinic, P1̄ (no. 2), a = 11.8934(5) Å, b = 12.0041(4) Å, c = 12.4578(5) Å, α = 68.718(4)°, β = 64.205(4)°, γ = 87.053(3)°, V = 1480.09(12) Å3, Z = 1, Rgt(F) = 0.0326, wRref(F2) = 0.0626, T = 293(2) K.